The alterations of oral, airway and intestine microbiota in chronic obstructive pulmonary disease: a systematic review and meta-analysis - Kou, Ziwei; Liu, Kai; Qiao, Zhengtong; Wang, Yaoyao; Li, Yanmiao; Li, Yinan; Yu, Xinjuan; Han, Wei (Frontiers in Immunology, 2024)
Background：Increasing evidence indicates the microbial ecology of chronic obstructive pulmonary disease (COPD) is intricately associated with the disease's status and severity, and distinct microbial ecological variations exist between COPD and healthy control (HC). This systematic review and meta-analysis aimed to summarize microbial diversity indices and taxa relative abundance of oral, airway, and intestine microbiota of different stages of COPD and HC to make comparisons.Methods：A comprehensive systematic literature search was conducted in PubMed, Embase, the Web of Science, and the Cochrane Library databases to identify relevant English articles on the oral, airway, and intestine microbiota in COPD published between 2003 and 8 May 2023. Information on microbial diversity indices and taxa relative abundance of oral, airway, and intestine microbiota was collected for comparison between different stages of COPD and HC.Results: A total of 20 studies were included in this review, involving a total of 337 HC participants, 511 COPD patients, and 154 AECOPD patients. We observed that no significant differences in alpha diversity between the participant groups, but beta diversity was significantly different in half of the included studies. Compared to HC, Prevotella, Streptococcus, Actinomyces, and Veillonella of oral microbiota in SCOPD were reduced at the genus level. Most studies supported that Haemophilus, Lactobacillus, and Pseudomonas were increased, but Veillonella, Prevotella, Actinomyces, Porphyromonas, and Atopobium were decreased at the genus level in the airway microbiota of SCOPD. However, the abundance of Haemophilus, Lactobacillus and Pseudomonas genera exhibited an increase, whereas Actinomyces and Porphyromonas showed a decrease in the airway microbiota of AECOPD compared to HC. And Lachnospira of intestine microbiota in SCOPD was reduced at the genus level.The majority of published research findings supported that COPD exhibited decreased alpha diversity compared to HC. However, our meta-analysis does not confirm it. In order to further investigate the characteristics and mechanisms of microbiome in the oral-airway-intestine axis of COPD patients, larger-scale and more rigorous studies are needed. The systematic review was registered with PROSPERO (https://www.crd.york.ac.uk/prospero/) as CRD42023418726.